PROFESSIONAL TRAINING OF SPECIALISTS FOR THE SELECTION OF PRIORITY SECTORS FOR IMPLEMENTATION OF CIRCULAR ECONOMY IN THE REPUBLIC OF POLAND - Oleksii Sysoiev (Borys Grinchenko Kyiv Metropolitan University, 2020)
The article considers analysis the content component of professional training for the selection of priority sectors for the introduction of the circular economy in the Republic of Poland. It is emphasized that the study of the experience of the Republic of Poland, which has taken an active position in the development of the circular economy and professional training for its implementation, is important for Ukraine given its proximity territorially, historically and cultural heritage. It is emphasized that in the process of accelerating the transition to a circular economy, education and training of specialists to implement the goals and objectives of the circular economy, which are fully consistent with the goals of global sustainable development, are quite important factors. It is proved that the training of specialists in circular economics for forecasting, for the ability to see in which sector of economic activity can get the most effective results not only in terms of economic effect, but also the preservation of the environment and public health is important. It is concluded that the professional training of specialists in circular economy should be aimed at the formation of knowledge about: factors taking into account the priority of the industry for the introduction of circular economy; application of business models of circular economies; methodologies of evolutionary nature of activity; evaluation methods by means of expert evaluation; opportunities to implement specific models of the circular economy in Polish realities; adaptation of business models to certain industries taking into account the context of the Polish market; adaptation of circular business models to priority industries from the point of view of the circular economy in Poland.